Genetic diversity in terapy bean (Phaseolus acutifolius) landraces grown in Botswana - Molosiwa, Odireleng O.; Kgokong, S.B.; Makwala, B.; Gwafila, C.; Ramokapane, M.G. (Academic Journals, 2014)
A field experiment was conducted at Department of Agricultural Research in Sebele in the 2012 to 2013 season using nine accessions that were sourced from the National Plant Genetic Resource Centre (NPGRC), Gaborone, Botswana. Multivariate statistical procedures such as clusters and principal component analysis were used on 15 selected characters to assess agro-morphological variability among tepary bean landraces collected in Botswana. Few characters were statistically significant which suggest lower genetic diversity among the Botswana tepary beans. The first three PCA accounted for 77.12% of accumulated variation. Traits which revealed significant contribution to variation among accessions were number of leaves, plant spread, pod width, 100 seed weight and seeds per pod. The dendrogram results also showed that these characters contributed significantly to the grouping of accessions into three clusters. Three accessions GK011, MTS (Motsumi) and GK012 were separated from the rest of the accessions. However, GK012 and MTS (Motsumi) with highest number of valuable traits are recommended for plant breeders to use as parents in future breeding programs.